2007
DOI: 10.1590/s0103-50532007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of nitric acid in the oxidative pretreatment step for preparation of humic acids from low rank coal of Mukah, Sarawak

Abstract: O ácido nítrico é um material eficiente na produção de ácidos húmicos. Contudo, é um item caro que torna o processo desfavorável industrialmente. Estudos indicaram que existe a possibilidade de re-utilização do ácido nítrico para oxidação; entretanto, as estruturas resultantes dos ácidos húmicos não foram estudadas. Por isso, o objetivo deste estudo foi investigar as propriedades espectroscópicas e químicas dos ácidos nitro-húmicos preparados com ácido nítrico re-utilizado. A amostra de carvão foi oxidada com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Humic acid compounds play an important role in improvement of physical, chemical and biological conditions of the soil as well as its role in activation of plant growth (Gomma & Youssef, 2008, El-Razek et al, 2012and Ahmed et al, 2013. Potassium humate is a highly concentrated form and inexpensive soluble salts of humus in the naturally occurring lignite which is the brown coal that accompanies coal deposits (Fong et al, 2007). Gulser et al (2010) found that Application of humic acid and calcium nitrate significantly affected seedling pepper growth by increasing fresh and dry leaf weight, fresh and dry root weight, stem diameter, root length and shoot length.…”
Section: Introductionmentioning
confidence: 99%
“…Humic acid compounds play an important role in improvement of physical, chemical and biological conditions of the soil as well as its role in activation of plant growth (Gomma & Youssef, 2008, El-Razek et al, 2012and Ahmed et al, 2013. Potassium humate is a highly concentrated form and inexpensive soluble salts of humus in the naturally occurring lignite which is the brown coal that accompanies coal deposits (Fong et al, 2007). Gulser et al (2010) found that Application of humic acid and calcium nitrate significantly affected seedling pepper growth by increasing fresh and dry leaf weight, fresh and dry root weight, stem diameter, root length and shoot length.…”
Section: Introductionmentioning
confidence: 99%
“…Humic acids are responsible for pH adjustment, enhancing soil cation exchange capacity and extending the survival mechanism of plants grown under stress conditions such as salinity, drought and harmful effects of toxic and heavy metal elements in the soil (Fagbenro and Agboda, 1983;David et al, 1994;Stevenson, 1994;Dursun et al, 1998;Pilanali and Kaplan, 2003;Sharrif, 2002;Kolsarici et al, 2005;Fong et al, 2007;Buyukkeskin and Akinci, 2011;Khaled and Fawy, 2011) In the present study, the salt-sensitive plant mung bean was subjected to the following treatments: a set of replicates watered only with Hoagland and Arnon (1950) solution (HO); two experimental sets exposed to 50 and 100 mM salt (NaCl) concentrations; and the remaining two sets of replicates exposed to the same two salt solutions with added 10 ml humic. The five different growth media replicates were tested for growth and physiological changes in mung bean seedlings, to determine the remediative role of humic acid on growth parameters and the mineral composition of both under and above ground parts of seedlings in all treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen content was measured as the residue (100% minus the content of C, H, N and S). The elemental composition was further used to calculate the oxidation index (ω) and hydrogen deficiency (ϕ) (Fong et al 2007).…”
Section: Methodsmentioning
confidence: 99%